Comparison of Reproductive Performance of the Roe Deer (Capreolus capreolus, L.) Among Different Regions - Majzinger, István (Acta Agraria Debreceniensis, 2006)
The potential and actual number of offspring of roe deer and the difference between these figures (prenatal and postnatal loss) significantly vary in each population yearly. The objective of this study is to examine the potential and actual number of offspring, the number of losses, and to find a link between the most important biological characteristics of does (body weight – BW, condition – KFI) and the number of raised offspring on four territories on the Great Hungarian Plain. Where the number of corpora lutea (CL) is the highest, there the losses are the highest as well, and the number of raised offspring is the lowest (region I.). Here, the rearing loss is double that of the weakest territory (region IV.). Rearing losses can be associated with the fenotype of does (BW, KFI) but environmental factors also have determinative importance. Where the number of twin-calving does was the highest, I found four times more does without a fawn than where the number of twin-calving does was the lowest. The nursing success was the best (the losses were lowest) in the region where the potential offspring (number of CL) was also the lowest, but the coverage of the habitat and the proportion of forests were largest. The food supply for the animals in autumn and winter are not enough, the structure of the habitat has to be improved as well, so that it might become adequate for game protection in extreme weather conditions. The results have to be considered as preliminary ones. It is essential to continue and extend the research to increase the reliability of the results.